Analisis Teoritis Fenomena Calon Tunggal Kota Samarinda Berdasarkan Konsep Kompetisi Politik Joseph Schumpeter - Rayhan Raditya; Niken Nurmiyati; Anwar Alaydrus; Asbudi Asbudi (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This article aims to conduct a theoretical analysis of the phenomenon of single candidates in the Samarinda City regional head elections, using Joseph Schumpeter’s concept of political competition. The method employed in this study is a descriptive qualitative method with a theoretical analytical approach. This study utilises secondary data obtained through a literature review, comprising books, academic articles, official news reports, official websites, and various documents relevant to the subject of study. Data analysis was conducted conceptually by examining and linking Joseph Schumpeter’s theory of political competition with the empirical conditions observed in the single-candidate phenomenon in Samarinda City. Through this approach, this study seeks to provide a comprehensive understanding of the alignment between theoretical concepts and the empirical realities unfolding on the ground. The findings indicate that the phenomenon of a single candidate in the Samarinda regional elections reflects a crisis of electoral competition due to the dominance of the incumbent, large party coalitions, and weak party cadre development. Procedurally, this situation is still considered legitimate as the election was conducted in accordance with the applicable regulations. However, within the framework of Schumpeterian political competition, the 2024 Samarinda mayoral election essentially fails to meet the criteria of procedural democracy, as there was no competition amongst political elites during its conduct.